2004
DOI: 10.1016/j.jacc.2004.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced nephropathy in patients undergoing primary angioplasty for acute myocardial infarction

Abstract: Contrast-induced nephropathy frequently complicates primary PCI, even in patients with normal renal function. It is associated with higher in-hospital complication rate and mortality. Thus, preventive strategies are needed, particularly in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
502
14
23

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(573 citation statements)
references
References 41 publications
34
502
14
23
Order By: Relevance
“…Patients with CKD stages 4 and 5 had the lowest utilization of PCI for NSTEMI treatment. This may be partially explained by fear of increased risk of contrast‐induced nephropathy transitioning to dialysis 25, 34, 35, 36. Using propensity score–matched NSTEMI admissions, our results demonstrated that the incidence of AKI requiring hemodialysis was significantly higher among NSTEMI patients admitted with CKD stage 4 who underwent PCI compared with those who did not; however, our study database did not allow us to define the timing of AKI relative to when PCI was performed.…”
Section: Discussionmentioning
confidence: 70%
“…Patients with CKD stages 4 and 5 had the lowest utilization of PCI for NSTEMI treatment. This may be partially explained by fear of increased risk of contrast‐induced nephropathy transitioning to dialysis 25, 34, 35, 36. Using propensity score–matched NSTEMI admissions, our results demonstrated that the incidence of AKI requiring hemodialysis was significantly higher among NSTEMI patients admitted with CKD stage 4 who underwent PCI compared with those who did not; however, our study database did not allow us to define the timing of AKI relative to when PCI was performed.…”
Section: Discussionmentioning
confidence: 70%
“…10 However, CIN incidence can be predicted via some risk-scoring methods. 10,12,13 Abbreviations: ACEI, angiotensin-converting enzyme inhibitor; ARB, angiotensin II receptor blocker; BMI, body mass index; Cr, creatinine; CrCl, creatinine clearance; DM, diabetes mellitus; F, female; LDL-C, low-density lipoprotein cholesterol; LVEF, left ventricular ejection fraction; M, male; NAC, N-acetylcysteine. Data are presented as mean ± SD or number and percentage of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, our study is the only prospective trial that provides data on the long-term outcome of patients with and without CIN. This is of considerable clinical relevance because the reported CIN-associated in-hospital and long-term mortality rates appear to be very high (2,3,5,6,15,16,18), while longterm data concerning this aspect are rare and have been derived only from small retrospective studies (2,3,5,6).…”
Section: Discussionmentioning
confidence: 99%
“…The glomerular filtration rate (GFR) was estimated using the Modification of Diet in Renal Disease equation (11) In accordance with other studies (1,3,4,9,(12)(13)(14)(15)(16)(17), CIN was defined as an increase in serum creatinine of 44.2 μmol/L (0.5 mg/dL) or more within 72 h after the administration of the contrast agent. Creatinine levels at 30 days, which were 44.2 μmol/L or more above the baseline creatinine level before heart catheterization, were classified as elevated creatinine levels at 30 days.…”
Section: Definitionsmentioning
confidence: 99%